The zebrafish embryo derivative affects cell viability of epidermal cells: A possible role in the treatment of psoriasis - Norata, Giuseppe; Biava, P.; Di Pierro, F. (2013)
In patients affected by psoriasis, use of a topical formula containing a derivative of zebrafish embryos was associated with reduced skin inflammation and dermal turnover, as well as a generally better outcome. In an attempt to understand the molecular mechanisms lying beyond these findings, we investigated the anti-proliferative effects of the zebrafish embryos derivative by addressing the mitochondrial function (MTT assay) and cell nuclei distribution (Hoestch staining). In cell cultures stimulated with fetal calf serum (FCS) or epidermal growth factor (EGF), the zebrafish derivative significantly inhibited cell proliferation induced by either approach, although the effect was stronger in cells stimulated with FCS. These results suggest that the zebrafish embryos derivative may dampen increased cell proliferation; this observation may be relevant to cutaneous pathologies related to altered proliferative mechanisms, including psoriasis.